A clinical study on the application of three-dimensionally printed splints combined with finite element analysis in paediatric distal radius fractures - Xu, Cheng; Wang, Lefeng; Zhang, Meng; Li, Xiao; Li, Kuang (Frontiers in Pediatrics, 2025)
PurposeThis single-centre randomised clinical trial assessed the clinical efficacy and patient satisfaction of 3D-printed splints optimised via finite element analysis (FEA) for pediatric distal radius fractures.MethodsThis retrospective study included 56 children diagnosed with forearm fractures at our hospital between August 2023 and August 2024. Those who underwent traditional U-shaped forearm plaster immobilisation were compared with those who received a customised 3D-printed splint. FEA was conducted based on the biomechanical characteristics of the forearm; the splint structure was optimised based on the analysis results and created via 3D printing. Outcomes were evaluated using the Patient Satisfaction Questionnaire and Wong-Baker Faces Pain Scale–Revised. Forearm function was evaluated using the Mayo Wrist Score and radiological outcomes. A power calculation was not performed due to the exploratory scope and resource limitations of this preliminary study.ResultsThe treatment costs significantly differed between the two groups (p = 0.001). In the Patient Satisfaction Questionnaire, the hot and sweaty item showed no significant difference (p = 0.089), whereas the last week's comfort (p = 0.001), first applied comfort (p = 0.004), weight (p = 0.001), itchiness (p = 0.015), smell (p = 0.003), and overall satisfaction items significantly differed between the two groups (p = 0.004). A comparison of the Mayo Wrist Score showed a statistically significant difference between the two groups after external fixation removal (p = 0.044). There were no significant differences between the two groups in terms of the palmar tilt angle (p = 0.196), ulnar deviation angle (p = 0.460), or height of the radial styloid (p = 0.111).ConclusionBoth 3D-printed splint and plaster cast fixation methods can effectively treat distal radial fractures in children, but the 3D-printed splint showed superior patient acceptance.